PERSEPSI WISATAWAN DOMESTIK MILENIAL TERHADAP KUALITAS DESA CANGGU SEBAGAI DESTINASI PARIWSATA DI BALI - Putu Haris Chandra Hartana; Dewa Ayu Made Lily Dianasari; Luh Nyoman Tri Lilasari (JURNAL KEPARIWISATAAN, 2022)
The quality of tourist destinations is one of the important things for the success of Canggu Village as a tourist destination in Bali. Perception is the process of a person how to selects, organizes, and interprets input information to create a meaningful overall picture. The existence of a good tourist perception of Canggu Village will affect return visits, as well as indirect promotion media among tourists. This study aims to determine the perception of millennial domestic tourists on the quality of Canggu Village as tourist destination in Bali. The sampling technique used purposive sampling technique with 96 tourists as respondents. For the analysis technique using quantitative descriptive analysis technique by looking for the average value of each variable. The perception of millennial domestic tourists who visited Canggu Village showed good results on the quality of Canggu Village as a tourism destination in Bali with a score of 3.68 included in the good category and including a positive value, while the lowest variable value was accessibility with a score of 3.21 including neutral value and fairly good value category.